Spatial Pattern of Rural Ecological Land and Its Multidimensional Gradient Differentiation in a Loess Hilly Region: A Case Study of Longxi County, Gansu Province, China - Ma, Libang; Yao, Yao; Tao, Tianmin; Zong, Yanling (Frontiers in Environmental Science, 2022)
Studying the gradient differentiation of rural ecological land (REL) from a microscopic perspective is conducive to the pattern optimization, scientific control, and protection of REL. This has far-reaching significance for the improvement of village appearance and the delineation of an ecological safety network. Taking Longxi County as an example, this research studied the spatial pattern of REL based on the landscape pattern index and analyzed the multi-dimensional gradient spatial differentiation characteristics of REL. Therefore, we can clarify the impact of natural and human factors on EL under different gradients. The results show 1) the rural ecological background conditions of Longxi County are good, and the area of ecological land (EL) accounts for 90.45% of the total area of the county; 2) there are significant differences between the spatial feature index and spatial pattern of REL in Longxi County. Its diversity, dominance, and shape index were mainly at low and medium levels. The degrees of fragmentation were mainly at low and high levels; and 3) the REL in Longxi County has different evolution laws in different gradients.